A study of the instructional courses in the professional education of elementary teachers in Ceylon - Fernando, Newton E. (s.n.], 1970)
The purpose of the study is to investigate the adequacy of the instructional courses in professional education offered by teacher colleges for elementary teacher education in Ceylon with a view of making suggestions for the improvement of these courses in order to make them more effective, adequate and up to date.